Agronomic and economic benefits of rice–sweetpotato rotation in lowland rice cropping systems in Uganda - Kyalo, G.; Rajendran, S.; Alibu, S.; Zziwa, S.; McEwan, M.; Ekobu, M.; Okello, S.E.A.; Namanda, S.; Otim, M.H.; Lamo, J.; Mwanga, R.O.M.; Low, Jan W. (Walter de Gruyter GmbH, 2024)
A crop rotation study was conducted in the Agoro Rice scheme from mid-2015 to 2017 to determine the effect of sweetpotato–rice rotation in the lowlands on financial returns and sweetpotato root, sweetpotato vine, and rice yields compared to monocropping. Treatments included crop rotations of sweetpotato–rice–sweetpotato, rice–sweetpotato–rice, rice–rice–rice (control), and sweetpotato–sweetpotato–sweetpotato (control). The study used the sweetpotato varieties NASPOT 11 (cream-fleshed), NASPOT 10 O, and Ejumula (both orange-fleshed) and the rice varieties Wita 9, Agoro, and Komboka. The results showed that mean sweetpotato root yields in the rotation treatment were significantly higher (28 t ha−1) than the control (19.8 t ha−1), representing a 47% gain in yield. Generally, the percentage gain in yield across years due to rotation ranged from 3 to 132%, depending on the variety. The total number of vine cuttings was significantly different between treatments and seasons (P < 0.001). Mean rice paddy yields in rotation were 8–35% higher than the control. The higher yields of sweetpotato in the rotation can be attributed to the rotation crop benefitting from residual fertilizers applied in rice in the previous season, while rice in the rotation crop could have benefited from the land preparation and establishment of the sweetpotato fields. The benefit of rotation for both crops varied by variety while the revenue-to-cost ratio varied by season and crop variety. Revenue-to-cost ratios for rotation and control treatments were greater than 1, indicating net profits were positive for both. The rotation generated 0.43 times more revenue than rice monocropping. Both rotation and monocropping systems generated profits, but rotation was 43% more profitable. In other words, if monocropping generates 1 dollar, rotation generates 1.43 dollars. The study concludes that rotation of sweetpotato with rice led to (1) increased yields of both rice and sweetpotatoes, (2) more profitable utilization of land, (3) enhanced availability of sweetpotato planting material at the beginning of the upland growing season, and (4) reduced the cost of land preparation for the main rice crop. Findings from this study show that there is great potential for diversification of rice-based cropping systems in Uganda, which will contribute to building sustainable food systems.